Two seasons of tick paralysis in Victoria yet one season in Queensland and New South Wales, Australia. Issue 1 (January 2023) - Teo, Ernest J.M.; Arganda, Alexa; Webster, Robert; Yappa, Amanda; Barker, Dayana; Barker, Stephen C.
Graphical abstract: Highlights: One season of tick paralysis in Queensland and New South Wales, Australia, yet two seasons in Victoria, Australia. Victoria has one season of tick paralysis in autumn, and another in spring. In Victoria, the number of cases of tick paralysis in the two seasons are negatively correlated. The negative correlation between seasons in Victoria may be due to immunity to Ixodes holocyclus acquired by dogs and cats. The seasons of tick paralysis start earlier in more northerly latitudes and later in more southerly latitudes. Abstract: We studied 22, 840 cases of tick paralysis in dogs and cats that were attributable to infestation with the eastern paralysis tick, Ixodes holocyclus . We report that the mortality rates from the holocyclotoxins of the tick or from euthanasia due to complications arising from tick paralysis in dogs and cats were 10% and 8%, respectively. The distribution of cases of tick paralysis among the 52 weeks of 22 years (1999 to 2020, inclusive) in four regions along the eastern coast of Australia revealed much about how the life-cycle of this tick varied among regions. The four regions in our study were: (i) Cairns, Innisfail, and surrounding postcodes in Far North Queensland; (ii) South East Queensland; (iii) Northern Beaches of Sydney in New South Wales; and (iv) the Shire of East Gippsland in Victoria. We found that the season of tick paralysis started earlier in more northerly latitudes than in more southerly latitudes. We also found that Victoria has two seasons of tick paralysis, one from approximately the third week of February to the first week of May, and another from approximately the third week of September to the third week of December, whereas all of the other regions we studied in eastern Australia only had one season of tick paralysis. When we studied the two seasons of tick paralysis in Victoria, we found a statistically significant negative correlation between the number of cases of tick paralysis between the two seasons: the more cases in one season, the fewer the cases in the next season. One possible explanation for the negative correlation may be immunity to I. holocyclus acquired by dogs and cats in the first season.